Characteristics of an NDM-1-producing Klebsiella pneumoniae strain belonging to ST105 - Wen Li; Yutong Liu; Yaxu Len; Li Xiang; Caixia Xin; Renjing Hu; Alberto J. Martín-Rodríguez; Bangqiong Weng; Yingshun Zhou (Antonie van Leeuwenhoek, 2026)

Antibiotic Alternative Strategies Against Aeromonas hydrophila Infections: New Trends and Advances - Shengping Li; Jing Dong; Shun Zhou; Bo Cheng; Xiaohui Ai (Reviews in Aquaculture, 2026)
Aeromonas hydrophila ( A. hydrophila ), an opportunistic pathogen widely distributed in aquatic environments and foods, is a serious threat to aquatic animals and even human health. Driven by the A. hydrophila diseases, various prevention and treatment strategies have gradually emerged. In this study, we reviewed the advances in the prevention and treatment of A. hydrophila diseases, including antibiotics, plant extracts, essential oils, phages, antimicrobial peptides (AMPs), probiotics, vaccines, disinfectants, and combination therapy. Although many prevention and treatment studies have been reported, A. hydrophila infection remains a problem. Therefore, we summarized some reports with significant in vivo therapeutic effects against A. hydrophila infections and provided several suggestions to help translate reported tools into clinical applications, and further predict potential artificial intelligence‐ and synthetic biology‐based prevention and control strategies in the future. As a result, this review provides a reference for the clinical prevention and treatment of A. hydrophila infections and research ideas for researchers in the future.